Crabhole Mosquito, Deinocerites cancer Theobald (Insecta: Diptera: Culicidae) - George F. O'Meara (EDIS)
This document is EENY-134, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2000.